ANALISIS KARAKTERISTIK DAN BIAYA KECELAKAAN LALU LINTAS DI KABUPATEN JEMBER - Karina Dea Puspita; Willy Kriswardhana; Nunung Nuring Hayati (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2020)
Jember regency has a population that is increasing every year, causing traffic density. However, the facilities did not get so much improvement as the population did, therefore the number of traffic accidents increased. A traffic accident has an impact to increase the amount of poverty because there is so much cost to spend, either cost for when the accident happened or after the accident happened for healing cost. This study aims to analyze the characteristics and costs of traffic accidents to reduce the number of traffic accidents in Jember using the Gross Output (Human Capital) method. The results of the Gross Output (Human Capital) method obtained the cost of accident victims in Jember for three years (2017-2019) of IDR 162,010,233,179 and the cost of traffic accidents in Jember for three years (2017-2019) of IDR 192,779,704,983.